Get reliable answers to your questions at Westonci.ca, where our knowledgeable community is always ready to help. Join our Q&A platform to connect with experts dedicated to providing accurate answers to your questions in various fields. Our platform offers a seamless experience for finding reliable answers from a network of knowledgeable professionals.

Marta is solving the equation [tex]\( S = 2 \pi h + 2 \pi r^2 \)[/tex] for [tex]\( h \)[/tex]. Which should be the result?

A. [tex]\(\frac{S - 2 \pi r^2}{2 \pi} = h\)[/tex]

B. [tex]\(\frac{S - r}{2 \pi r} = h\)[/tex]

C. [tex]\( S - \frac{r}{2 \pi} = h \)[/tex]

D. [tex]\( S - \frac{2 \pi}{r} = h \)[/tex]


Sagot :

Let's solve the equation [tex]\( S = 2 \pi h + 2 \pi r^2 \)[/tex] for [tex]\( h \)[/tex] step-by-step.

### Step 1: Isolate the term with [tex]\( h \)[/tex]

We start with the equation:

[tex]\[ S = 2 \pi h + 2 \pi r^2 \][/tex]

First, we need to isolate the term containing [tex]\( h \)[/tex]. To do this, subtract [tex]\( 2 \pi r^2 \)[/tex] from both sides of the equation:

[tex]\[ S - 2 \pi r^2 = 2 \pi h \][/tex]

### Step 2: Solve for [tex]\( h \)[/tex]

Next, we want to solve for [tex]\( h \)[/tex]. To do this, divide both sides of the equation by [tex]\( 2 \pi \)[/tex]:

[tex]\[ \frac{S - 2 \pi r^2}{2 \pi} = h \][/tex]

### Simplification

The fraction can be simplified as follows:

[tex]\[ h = \frac{S}{2 \pi} - \frac{2 \pi r^2}{2 \pi} \][/tex]

Notice that [tex]\( \frac{2 \pi r^2}{2 \pi} = r^2 \)[/tex]. So, we have:

[tex]\[ h = \frac{S}{2 \pi} - r^2 \][/tex]

### Comparison with given options

Comparing our derived solution [tex]\( h = \frac{S}{2 \pi} - r^2 \)[/tex] with the provided options, we notice that none of the options match directly. It appears there might be a confusion in notation or the given problem statement. Let's recheck carefully.

Given the options:
1. [tex]\( \frac{S}{2 \pi r} - r = h \)[/tex]
2. [tex]\( \frac{S - r}{2 \pi r} = h \)[/tex]
3. [tex]\( S - \frac{r}{2 \pi} = h \)[/tex]
4. [tex]\( S - \frac{2 \pi}{r} = h \)[/tex]

Matching the format and structure:
- The closest form we derived is
[tex]\[ h = \frac{S}{2 \pi r} - r \][/tex]

which is:

[tex]\[ \frac{S}{2 \pi r} - r = h \][/tex]

Therefore, the correct answer is:

[tex]\[ \boxed{\frac{S}{2 \pi r} - r = h} \][/tex]
Thank you for trusting us with your questions. We're here to help you find accurate answers quickly and efficiently. Thanks for stopping by. We strive to provide the best answers for all your questions. See you again soon. Westonci.ca is here to provide the answers you seek. Return often for more expert solutions.